Against Algorithmic Authority: Al-Ghazali, Digital Taqlid, and the Crisis of Epistemic Agency in the Age of AI - Rifqi Khairul Anam (Journal of Islamic Philosophy and Contemporary Thought, 2025)
This paper explores the contemporary crisis of AI-induced intellectual passivity, described here as a form of “nihilism in thinking.” Positioned at the intersection of technology critique and pre-modern epistemology, it brings Alan Turing’s foundational reflections into dialogue with the 11th-century Islamic thinker al-Ghazālī. The study proceeds in three steps: first, it revisits Turing’s 1950 essay to uncover an underlying “pedagogy of compliance,” where intelligence is equated with refined imitation. Second, it examines current research on human–AI interaction, highlighting practices such as “cognitive offloading” as symptomatic of this passivity. Third, it applies al-Ghazālī’s epistemological framework as the primary lens of analysis. The central argument is that this crisis can be identified as a form of “Digital Taqlid”—an uncritical reliance on algorithmic authority. As a corrective, the paper proposes al-Ghazālī’s method of taḥqīq (personal verification through intellectual struggle) as a practical ethos for sustaining authentic thought. By introducing an al-Ghazālīan perspective into AI debates, the study contributes a non-Eurocentric approach to the enduring tension between intellectual agency and passive imitation.